AN ANALYSIS OF DRAMATIC TECHNIQUE IN DEATH OF A SALESMAN BY ARTHUR MILLER - Rara Silvany Aulia; Ayu Melati Ningsih (PHILOLOGY Journal of English Language and Literature, 2026)
Arthur Miller’s Death of Salesman remains a seminal text in modern American drama, not merely for its narrative content but for its innovative use of dramatic style technique that mirror the protagonist’s psychological breakdown. While the play has been widely analyzed for its themes, less attention has been given to how its structure and style cause those themes to resonate with the audience. This study hypothesizes that Miller’s deliberate use of non-linear narrative (Flashback), expressionistic stage directions, and symbolic language serve as mechanisms to externalize Wily Loman’s mental deterioration and critique the American Dream. This research employs a qualitative, descriptive analytical design focused on close reading. The data source is the original 1949 script of Death of a Salesman. Key technique flashback. Stage direction, tone shifts are identified and analyzed using dramatology theory (Innes, 2000; Elam, 1980) and semiotic analysis (Barthes, 1967). Finding show that 70,6% of scene transitions employ non-linear shifts, especially flashbacks, correlating directly with moments of psychological tension. Dialogue analysis reveals 137 over symbolic references of failure and illusion. Stage direction demonstrate 276 unique-mood setting. Cues that enhance emotional atmosphere were identified 82.3%.